(untitled) (Eurasian Research Bulletin, 2023)
Our article Reading Technology for Selecting Instructional Activities to Read Aloud to 7th-Grade Students at Home describes several methods that can be used in an activitybased classroom. One of the biggest challenges I faced as an experienced English teacher in the classroom was teaching motivational reading. Of course, there are pre and posttalks and various ways to make accompanying comprehension and vocabulary tasks more enjoyable, but reading itself is an inherently quiet and solitary task. In addition, we try to teach our 7th-Grade Students the standard skills, such as B. Skim, scan, predict, and infer and guess vocabulary meanings from context, practice, practice, practice. Such exercises, while useful and necessary, can feel slightly repetitive, redundant, and downright boring.